The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1111/j.1547-5069.1999.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Social Support, and Quality of Life in Older Adults With Osteoarthritis

Abstract: Social support appeared to play an important role in moderating the effects of pain, functional limitation, and depression on these subjects' quality of life. Nurses who work with older adults are in a unique position to help them adjust to living with osteoarthritis by providing them the support needed to help them manage their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 34 publications
2
61
0
4
Order By: Relevance
“…In contrast, other studies have shown that social network/support may be weaker, especially among the oldest old, with increasing age 31,32 and hence the potential moderating influence on pain from the social network/support is not there anymore. 30,33,34 People in the social network can not only be supportive and help to manage daily life, but could also be helpful in identifying problems (e.g., pain) and in obtaining help. The oldest old (85ϩ) in pain, in this study, were more often found to live in sheltered housing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have shown that social network/support may be weaker, especially among the oldest old, with increasing age 31,32 and hence the potential moderating influence on pain from the social network/support is not there anymore. 30,33,34 People in the social network can not only be supportive and help to manage daily life, but could also be helpful in identifying problems (e.g., pain) and in obtaining help. The oldest old (85ϩ) in pain, in this study, were more often found to live in sheltered housing.…”
Section: Discussionmentioning
confidence: 99%
“…Pain was shown, through gait compensation studies of patients with osteoarthritis, to be correlated to decreased walking speeds, step rates and single limb stance, whilst also causing the individual to alter their gait pattern (Hurwitz et al, 1997). It is therefore an imperative that pain is managed appropriately for this patient group (Bliven and Kippes, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research investigating the psychometric properties of the QOLS indicates good test-retest reliability, internal consistency, and convergent and divergent validity (Burckhardt, Clark, & Bennett, 1993;Blixen & Kippes, 1999).…”
Section: Screening Measuresmentioning
confidence: 99%